DEVELOPMENT OF PADLET-BASED ENGLISH LEARNING MEDIA ON RECOUNT TEXT MATERIAL - Muhammad Rifqi Maulana; M Syadeli Hanafi; Cucu Atikah (Journal of English Educational Study (JEES), 2023)
This research is aimed at producing product in the form of material content developed in a web format in the form of a material page and assignment page to make students easily in the learning process. This study used the Research and Development (R&D) method with the 4D model as a guide for developing an effective product. The research procedure is to determine the learning requirements, design the required learning media, developed the learning media that had been designed, and disseminate the result of the product developed to students. The research results obtained in this study were the Padlet media feasibility test which scored 92.30% in the “Very Eligible” category for media validation and 93% in the “Very Eligible” category for material development. This development research showed that this Padlet media could involve students actively in the learning process.Keywords: Learning Media; Padlet; Recount Text